Optimized Power Flow Analysis of IEEE 14 Bus System Using Matlab - Hazarika, Sanjib (International Journal of Computer Sciences and Engineering, 2019)
For proper planning and operation of power system and economic scheduling of generating units, power flow analysis plays a vital role. It is performed to have clear knowledge regarding bus voltage magnitude and angle and line flows. A number of methods are being used all over the world for power flow analysis. Newton Raphson method, Gauss Seidal method, fast decoupled load flow methods are a few to name. Now days, various soft computing techniques are adopted by researchers as well as practicing engineers for load flow analysis to cater various needs of the research institutes and the utilities. Every method has got advantages as well as disadvantages. The objective of this paper is to develop an user friendly software to perform load flow analysis for IEEE 14 bus system. Optimization of IEEE 14 bus sytem has been performed using Particle Swarm Optimization Technique. The software will be helpful for researchers, practicing engineers, students of power system of various levels to carry out power flow quickly and efficiently as per their requirement. The software is developed using MATLAB programming.